Fiscal Dimensions of Sustainable Development. (Pamphlet Series; Pamphlet Series, ;, 2002)
Fiscal policy affects sustainable development through its effects on growth, the environment, and resource development. What are the relationships between fiscal policy and sustainable development, and how does the IMF seek to promote sustainable development in its policy advice? What lessons have been learned so far, and how can governments, the international community, and international financial institutions more fully support sustainable development?